A mitochondrial root to accelerated ageing and frailty - Ferrucci, Luigi; Zampino, Marta (Nature reviews. Endocrinology, 2020)
A discovery metabolomic study was performed in a large cohort of adults to identify circulating biomarkers of frailty. The study found that carnitine and vitamin E pathways were dysregulated in frail compared with non-frail participants. These findings point to dysregulated mitochondrial metabolism as a potential root of age-related frailty.